Customer Attitude Towards Green Banking Products And Services Provided By Public Sector Banks In Thiruvanthapuram District (International Journal of Food and Nutritional Sciences, 2022)
Green Banking also called as ethical or sustainable banking is a form of banking activity that reduces the negative impact on environment thereby protecting the scarce natural resources. Through this type of banking a country gets more environmental. The banking industry plays a vital and mediator role between economic growth of a country and its environmental protection through various products and services which makes the environment sustainable. The study aims to identify the factors influencing the customer attitude to use green banking products and services, the awareness level of the customers about the green banking products and the perception of risk towards using those products and services. The customers of public sector banks in Thiruvanthapuram district are taken for the study. This research is descriptive in nature. Primary data and secondary data were used for the study. Primary data was collected using a structured questionnaire and the secondary data from journals, websites, and news papers. The data was collected from 80 respondents belongs to the selected public sector banks from the Thiruvanthapuram District. The collected data were analyzed using percentage analysis, chi-squre test and Garret ranking in order to draw the inference of the study. The study concluded that the public sector banks shall create strong awareness among the customers about the green products and services which are provided by them. They shall externally influence the customers to use the green banking products for their financial transaction. Proper rewards and value added features will motivate the customers to use green banking. Digital literacy shall be provided by the banks to the customers to use green banking without any hesitation and on their own without the help of others. Banks have to take necessary steps for the effective use of green banking among the customers.